0170 Identifying Skill Level Differences In Simulated Laparoscopic Scenarios Under High And Low Attentional Demands. (1st November 2014) - Rees, Ben; McRobert, Allistair; Causer, Joe; Williams, Mark; Baxendale, Bryn
Abstract : Background/context: The acquisition of expertise requires that individuals develop complex, integrated systems of representations that facilitate the execution, monitoring, planning and analyses of performance. 1 In order to determine what constitutes expertise in surgery it is important to examine the underlying processes utilised by experts. Simulation technologies enable medical educators to examine these processes and determine key performance metrics that differentiate expert and less-expert surgeons. 2 Once identified, educators can design and implement specific training environments and interventions that enable the underlying processes and mechanisms to be developed via engagement in deliberate practice activities. Methodology: A sample of medical students and postgraduate students matched on demographic information, will perform a series of simulated laparoscopic procedures on a CAE Healthcare LapVR system. Eye movements, performance outcome, tool efficiency/kinematics, as well as heart rate will be recorded in low (primary task only) and high (primary and secondary task) attention scenarios as well as simple and complex procedures. Results/outcomes: We will present pilot data looking at a case study comparison of a surgeon against a non-medical participant. Based on previous research, 4 we expect the surgeon to perform better, have more efficient eye (fewer fixations of longer duration) and tool movements, and be less affected by an increase in attentional and complexity demands, compared to the non-medical participant. Breakdown in primary and secondary task performance is expected to occur in the complex high-attention condition. Potential Impact: By identifying the critical characteristics that are associated with expertise, training interventions can be designed and implemented to enhance the specific skills and necessary adaptations that are essential to expertise in medicine subsequently improving the quality of patient treatment and reducing the costs associated with healthcare. References: Causer J, Williams AM (2012). Professional expertise in medicine. In P. Lanzer (Ed.), Catheter-based Cardiovascular Interventions - Knowledge-based Approach (pp. 97–112). NY: Springer Causer J, Barach P, Williams AM. Expertise in medicine: using the expert performance approach to improve simulation training. Medical Education 2014;48(2):115–123 Causer J, et al . Performing Under Pressure: Quiet Eye Training Improves Surgical Knot-tying Performance. Surgery 2014 Zevin B, Aggarwal R, Grantcharov TP. Surgical Simulation in 2013: why is it still not the standard in surgical training? J Am Coll Surg 2014;218(2):294–301